Effects of diets on reproduction of angelfish, Pterophyllum scalare (Cichlidae) - Degani, Gad; Yehuda, Yehuda (Indian Journal of Fisheries, 2011)
The effects of various diets on spawning and egg quality were studied in Pterophyllum scalare (Cichlidae). The experiments were started after three spawnings of each pair, with six pairs to each diet. Diet 1 consisted of mosquito larvae (50% protein), diet 2 of turkey hearts (79% protein) and diet 3 of fish meal (57% protein). Each pair was fed 5 g per day, with the addition of 0.5 glive Artimia salina. The average interval between spawnings was shorter in fish fed diet 1 than in those fed diet 2; and diet 2 gave a shorter interval than diet 3. The differences were statistically significant. Similarly, there was a significant difference in the percentage of eggs hatched, with diet 1 giving the highest and diet 3 the lowest results. No significant difference was found between the experimental groups in the number of eggs spawned